Micro-tilt controlled rotating face-plate stage for sigle-point diamond turning - Mizuno, H. (Cranfield University, 1993)
The machining of brittle materials such as glasses and ceramics is an area of rising interest in the 'Precision Engineering' field due to the advantageous characteristics of ceramics and demands for glass machining from optical component manufacturers. In general the 'ductile mode' machining of brittle materials requires cut-geometry to be sub-micrometre. In order to improve machining accuracy of single-point diamond turning for brittle materials in the ductile mode, a controlled micro-tilt stage system was proposed for improvement of the motion accuracy and dynamic stiffness of an aerostatic spindle. Mechanical arrangements for the proposed controlled micro-tilt stage system including slip rings for transferring voltage signals to a rotating body were developed together with a strategy for spindle metrology using three optical fibre sensors. Algorithms for averaging and spacial filtering were applied to remove random noise caused by the variation of surface texture. The micro-tilt stage was designed to satisfy specifications in respect of travel range, resolution, stiffness, and resonant frequency. Efforts were also made to minimize static and dynamic cross-coupling-interference between the required three degrees of freedom. The micro-tilt stage showed satisfactory performance, and the effectiveness of non-crosscoupling design was seen. After considering various control strategies, hardware and software were arranged with PID and repetitive controllers. The diagonal dominance of the micro-tilt stage control system permitted 'SISO' system design. The performance of the controlled micro-tilt stage was investigated both stationary and during rotation. The stationary controlled micro-tilt stage worked satisfactorily; the controlled rotating micro-tilt stage demonstrated its error-correcting capability with some speed limitations, primarily due to the spacial filtering and time averaging required to reduce the surface texture noise.